1991
DOI: 10.1007/bf01284787
|View full text |Cite
|
Sign up to set email alerts
|

Rotational and single-particle structures in83Zr

Abstract: The band structure of 83Zr has been investigated using the Daresbury recoil separator and TESSA array with 20 Compton suppressed Ge detectors and the reaction 2SSi(SSNi, 2pn) at 195 MeV. DCO ratios have been used to make many new spin assignments. The three known rotational bands have been extended up to the onset of the five quasiparticle bands. On the basis of the 21/2 +, 23/2 + and 25/2 + yrast and yrare states, a (3qp) structure similar to those found in the isotones 79Kr and S~Sr has been identified. Addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…A total of 120 bands in 56 nuclei from four mass regions have been compiled from the literature. Some additional cases, namely 83 Y [28,29], 83 Zr [30], 106 Cd [31], 103,105,107,109 In [32,33], 117 I [34], 128 Ba [35], and 139 Pm [36], are also likely candidates of MR bands but have not been included in this Table due to the uncertain nature of the bands and insufficient information. The bands in the A ϭ 80 and 135 regions and Hg nuclides included in the Table should also be treated with caution.…”
Section: Discussionmentioning
confidence: 96%
“…A total of 120 bands in 56 nuclei from four mass regions have been compiled from the literature. Some additional cases, namely 83 Y [28,29], 83 Zr [30], 106 Cd [31], 103,105,107,109 In [32,33], 117 I [34], 128 Ba [35], and 139 Pm [36], are also likely candidates of MR bands but have not been included in this Table due to the uncertain nature of the bands and insufficient information. The bands in the A ϭ 80 and 135 regions and Hg nuclides included in the Table should also be treated with caution.…”
Section: Discussionmentioning
confidence: 96%
“…Our recent observations in 83Zr [14] and 84-87Nb [ Table 1 apply the DCO technique for making spin assignments [17]. We define the DCO ratio of transitions 9,1 via the expression Y(9,~ at 162~ gated with 9'2 at 65 ~ 115 ~ RDc~ Y(9,1 at 65 ~ 115~ gated with 9'2 at 162~ ' where the intensities Y have been corrected for both the efficiency of the observing and gating detector.…”
Section: Experimental Procedures and Data Reductionmentioning
confidence: 99%
“…A brief inspection of the summary DCO values plotted versus yray energy (Fig. 6) shows that there are two clearly separated groups of experimental values similar to those in a3zr [32] and 87Nb [12]. All the known pure quadrupole transitions and many of the newly identified lines in the energy range 400-2500 keV have DCO ratios about 1.0, so the situation for E2 transitions seems to be clear, when comparing the results with our previous measurements [12,321.…”
Section: Iib Dco Ratiosmentioning
confidence: 74%
“…The majority of the other DCO ratios is grouped around 0.5. Rudolph et al observed in 83Zr [32] a relatively separated third group of pure E 1 transitions having RDco~0.7. Thus the DCO ratios for dipole transitions seem to be very sensitive to the setup geometry when using only E2 gates.…”
Section: Iib Dco Ratiosmentioning
confidence: 96%
See 1 more Smart Citation